The THE EFFECT OF GEOLOGICAL STRUCTURES ON THE COAL QUALITY OF THE SEMBAKUNG FORMATION IN BERAU REGENCY, EAST KALIMANTAN - Sugiarto, Wahyu; R. A., T. Listiyani; Hartono, Hill G.; Budiadi, Ev. (Institut Teknologi Nasional Yogyakarta, 2024)
The Subsurface coal resources are 43.533 billion tons with total reserves of 173.51 million tons. The Berau Regency area has coal-bearing formations of the bituminous - sub bituminous type, namely the Latih Formation, Labanan Formation, Domaring Formation, Sajau Formation and Sembakung Formation. The research methods used are surface geological mapping, rock sampling and drilling. The analysis used is coal quality and geological structure. The results of analysis of changes in the dip of rock layers caused by geological structures in the form of folds and thrust faults can cause changes in coal quality. The dip of coal seam in the LP 54 outcrop sample is 24º, which has lower coal quality compared to LP 38 that has a seam dip of 65º. The quality of coal in LP 38 seam position N 203º E/65º has a calorific value of 6,393 Kcal/kg, while in LP 54 seam position N 30º E/24º has a calorific value of 4,888 Kcal/kg. At the drill point, location MMA_19-T has better coal quality compared to MMA_18-T and MMA_20-T, this is because the seam in MMA_19-T experienced folding accompanied by faulting with a calorific value of 7326 Kcal/kg.